RESILIENT WOMEN TO OVERCOME ADVERSITIES IN BETTY SMITH’S A TREE GROWS IN BROOKLYN - Jangir, Helan; Mahmoud , Amel (Humanities Journal of University of Zakho, 2025)
The current article explores vital thematic elements in Betty Smith’s novel A Tree Grows in Brooklyn (1943). The analysis concentrates on the protagonist of the novel who is an eleven-year-old Francie Nolan along with other key female members of her big family; mother, aunts and grandmother. These female characters distinctly reveal sturdy personalities and inner strength as they grapple with financial hardships, limited opportunities, and social difficulties. In the current article, the discussion thoroughly inspects three key aspects in this novel. The first is the sturdy spirit of resilience among the female family members of the protagonist, Francie. Second, the utilization of the varied skills of being resourceful and innovative in managing the daily needs of life for the poor families, Francie’s family being one among those. Third, the firm ties of solidarity among the female members of Francie’s family, the grandmother and the aunts, and among the women of the neighbourhood in order to withstand the diverse challenges. In the current article, the analysis places special focus on the personality of the young protagonist Francie in her relentless efforts to prevail over her adverse circumstances through sharpening her resilient spirit, bolstering her skills of resourcefulness and enhancing ties of solidarity.